มาตรการในการควบคุมการโฆษณาเครื่องดื่มแอลกอฮอล์ ตามพระราชบัญญัติเครื่องดื่มแอลกอฮอล์พุทธศักราช 2551 Measures of controlling alcohol advertisements in accordance with the alcohol control Act B.E. 2551 - ณ นคร, จักกฤษ (Academic Journal Phranakhon Rajabhat University, 2017)
บทคัดย่อ การทำวิจัยครั้งนี้มีวัตถุประสงค์ที่จะศึกษาถึงกฎหมายที่เกี่ยวกับการควบการโฆษณาเครื่องดื่มแอลกอฮอล์ตามพระราชบัญญัติเครื่องดื่มแอลกอฮอล์ พ.ศ. 2551 เนื่องจากคนไทยมีแนวโน้มในการบริโภคเครื่องดื่มแอลกอฮอล์เพิ่มสูงขึ้นในทุกเพศทุกวัยส่วนหนึ่งอาจเป็นเพราะการโฆษณาประชาสัมพันธ์เครื่องดื่มแอลกอฮอล์ ดังนั้นกฎหมายที่เกี่ยวกับการควบคุมการโฆษณาเครื่องดื่มแอลกอฮอล์ถือเป็นเรื่องที่มีความสำคัญที่ผู้วิจัยได้ทำการศึกษา โดยผู้วิจัยได้ใช้ระเบียบวิธีวิจัยเอกสารเพื่อทำการศึกษาวิเคราะห์ข้อมูล ให้สอดคล้องกับสมมุติฐานของการวิจัยและกรอบแนวคิดในการวิจัย โดยศึกษาจากแนวคิด ทฤษฎีกฎหมายที่เกี่ยวข้อง คำพิพากษา บทความต่างๆที่เกี่ยวกับการควบคุมการโฆษณาเครื่องดื่มแอลกอฮอล์ของประเทศไทยเปรียบเทียบกับกฎหมายของต่างประเทศ และผู้วิจัยได้ทำการสัมภาษณ์ สอบถามบุคคลกลุ่มตัวอย่างที่มีส่วนเกี่ยวข้องกับมาตรการในการโฆษณาเครื่องดื่มแอลกอฮอล์อาทิเช่น ประชาชนโดยทั่วไป หน่วยงานภาครัฐที่เกี่ยวข้อง ผู้ประกอบการธุรกิจด้านการโฆษณาเครื่องดื่มแอลกอฮอล์ และผู้ที่มีความรู้ด้านกฎหมาย นักวิชาการผลจากการวิจัย เมื่อได้วิเคราะห์ถึงกฎหมายที่เกี่ยวกับการควบคุมการโฆษณาเครื่องดื่มแอลกอฮอล์ตามพระราชบัญญัติเครื่องดื่มแอลกอฮอล์ พ.ศ. 2551 เปรียบเทียบกับกฎหมายที่เกี่ยวกับการควบคุมการโฆษณาเครื่องดื่มแอลกอฮอล์ของต่างประเทศแล้วพบว่ากฎหมายที่เกี่ยวกับการควบคุมการโฆษณาเครื่องดื่มแอลกอฮอล์ของประไทยในมาตรา 32 แห่งพระราชบัญญัติเครื่องดื่มแอลกอฮอล์ พ.ศ. 2551 ยังไม่สามารถที่จะควบคุมการโฆษณาเครื่องดื่มแอลกอฮอล์ได้ดี เนื่องจากในปัจจุบันผู้ประกอบการธุรกิจมีวิธีการโฆษณา การสื่อสารทางการตลาด และการส่งเสริมการขายที่หลากหลายไม่ว่าทางตรงหรือทางอ้อม สถิติของผู้ดื่มแอลกอฮอล์จึงเพิ่มขึ้น ซึ่งต่างจากกฎหมายของต่างประเทศที่มีกฎหมายที่เกี่ยวกับการควบคุมการโฆษณาเครื่องดื่มแอลกอฮอล์ที่ละเอียดและรัดกุมในแง่ของตัวบทกฎหมายมากกว่าของประเทศไทยส่งผลให้การควบคุมการโฆษณาเครื่องดื่มแอลกอฮอล์มีประสิทธิภาพมากกว่าด้วย ทั้งนี้ เพื่อที่จะทำให้มาตรการในการควบคุมการโฆษณาเครื่องดื่มแอลกอฮอล์ตามพระราชบัญญัติเครื่องดื่มแอลกอฮอล์ พ.ศ. 2551 มีประสิทธิภาพยิ่งขึ้นควรมีการปรับปรุงแก้ไขกฎหมายดังกล่าว Abstract This research is aimed to study regulations concerning alcohol advertisement control under The Alcohol Control Act B.E. 2551 as consumption of alcohol is evidently rising. There is the fact that the high number of alcohol drinkers partially resulted from advertisements. Accordingly, the measures used to monitor the advertisements are the crucial subject to examine. In this study, I have investigated legal theories, verdicts, journals and legal regulations relating to alcohol advertisement control in Thailand perspective in comparison with foreign countries approaches. Moreover, the questionnaires and interviews applied to be the methodologies in order to obtain several ideas on how effectively the Alcohol Control Act is. Participants who took part in answering the questionnaires, as well as cooperated in the interviews, were somewhat relevant to alcohol consumption or alcohol control policy makers. The finding found that in Article 32 of the Alcohol Control Act of Thailand failed to control the alcohol adverts because the regulations merely applied to traditional way of advertising, while these day the adverts comes in different forms. The entrepreneurs seem to be more creative and tend not to promote their products traditionally. They highly use indirect ways of marketing to boost their sales. As a result, the number of new drinkers has increased. On the other hand, other countries' approaches about alcohol control are more strictly enforced and cover a wider range of marketing and advertising monitor. Therefore the study showed the inclination in number of alcohol drinkers. In conclusion, to control alcohol advertisement efficiently, the regulations must be amended. As mentioned above, the entrepreneurs came up with new methods and schemes to marketing their products indirectly, hence measures handling this issue should be reregulated in order to respond to different circumstances.In conclusion, to control alcohol advertisement efficiently, the regulations must be amended. As mentioned above, the entrepreneurs came up with new methods and schemes to marketing their products indirectly, hence measures handling this issue should be reregulated in order to respond to different circumstances.